Trends in volume-regulated anion channel (VRAC) research: visualization and bibliometric analysis from 2014 to 2022 - Liu, Tianbao; Li, Yin; Wang, Dawei; Stauber, Tobias; Zhao, Jiajun (Frontiers in Pharmacology, 2023)
Objective: In this study, we utilized bibliometric methods to assess the worldwide scientific output and identify hotspots related to the research on the volume-regulated anion channel (VRAC) from 2014 to 2022. Methods: From Web of Science, we obtained studies related to VRAC published from 2014 to 2022. To analyzed the data, we utilized VOSviewer, a tool for visualizing network, to create networks based on the collaboration between countries, institutions, and authors. Additionally, we performed an analysis of journal co-citation, document citation, and co-occurrence of keywords. Furthermore, we employed CiteSpace (6.1. R6 Advanced) to analyzed keywords and co-cited references with the strongest burst. Results: The final analysis included a total of 278 related articles and reviews, covering the period from 2014 to 2022. The United States emerged as the leading country contributing to this field, while the University of Copenhagen stood out as the most prominent institution. The author with most publications and most citations was Thomas J. Jentsch. Among the cited references, the article by Voss et al. published in Science (2014) gained significant attention for its identification of LRRC8 heteromers as a crucial component of the volume-regulated anion channel VRAC. Pflügers Archiv European Journal of Physiology and Journal of Physiology-London were the leading journals in terms of the quantity of associated articles and citations. Through the analysis of keyword co-occurrence, it was discovered that VRAC is involved in various physiological processes including cell growth, migration, apoptosis, swelling, and myogenesis, as well as anion and organic osmolyte transport including chloride, taurine, glutamate and ATP. VRAC is also associated with related ion channels such as TMEM16A, TMEM16F, pannexin, and CFTR, and associated with various diseases including epilepsy, leukodystrophy, atherosclerosis, hypertension, cerebral edema, stroke, and different types of cancer including gastric cancer, glioblastoma and hepatocellular carcinoma. Furthermore, VRAC is involved in anti-tumor drug resistance by regulating the uptake of platinum-based drugs and temozolomide. Additionally, VRAC has been studied in the context of pharmacology involving DCPIB and flavonoids. Conclusion: The aim of this bibliometric analysis is to provide an overall perspective for research on VRAC. VRAC has become a topic of increasing interest, and our analysis shows that it continues to be a prominent area. This study offers insights into the investigation of VRAC channel and may guide researchers in identifying new directions for future research.